1994
DOI: 10.1111/j.1749-7345.1994.tb00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Egg Quality Determinants in Finfish The Role of Overripening with Special Reference to the Timing of Stripping in the Atlantic Halibut Hippoglossus hippoglossus

Abstract: Egg quality, those characteristics of the egg that determine its capacity to survive, is a significant problem for many species of fish currently being farmed. Little is known about the determinants of egg quality and there is little agreement regarding reliable methods for its assessment. To be of practical benefit, assessments should be simple to perform and should be carried out as early in development as is possible. Fertilization rates are often used as measures of quality. For the Atlantic halibut Hippog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 24 publications
5
73
0
2
Order By: Relevance
“…Since the various parameters and eggs characteristics that have been proposed as indicators of the spawning quality for fish seem to be able to define the spawning quality a combination of different criteria provide a better result. Some studies carried out in the wild have shown that food availability is the primary determinant of fertility, which can be defined as the number of mature eggs produced per female during the annual cycle of egg spawning (Wotton, 1979;Bromage et al, 1992.). Some studies have been conducted on aquatic species that inhabit freshwater rivers with different food availability, showed that fish living in rivers of low productivity, provides low fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Since the various parameters and eggs characteristics that have been proposed as indicators of the spawning quality for fish seem to be able to define the spawning quality a combination of different criteria provide a better result. Some studies carried out in the wild have shown that food availability is the primary determinant of fertility, which can be defined as the number of mature eggs produced per female during the annual cycle of egg spawning (Wotton, 1979;Bromage et al, 1992.). Some studies have been conducted on aquatic species that inhabit freshwater rivers with different food availability, showed that fish living in rivers of low productivity, provides low fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, viability during the early life stages depends mainly on egg quality, which is associated with the quantity of nutrients stored in the oocytes (Brooks et al, 1997). Bromage et al (1994) defi ned egg quality as "those characteristics of the egg that determine its capacity to survive." There are different methods and indices that can be used to estimate the quality of fi sh eggs.…”
Section: Maternal Effects On Fecundity and Egg Quality Of The Patagonmentioning
confidence: 99%
“…However, no differences were detected in terms of egg production and egg fertilization between females expose to SP and NP in this study. Many fish use the increasing and decreasing components of day length, transducing this information into a suitable message for integration by the neuroendocrine cascade which initiates and then modulates reproductive development (Bromage et al, 1994). In fact a reduction from long to short photoperiod is able to advance trout spawning (Randall et al, 1995).…”
Section: Discussionmentioning
confidence: 99%